DESIGN AND DEVELOPMENT OF BANANA FIBER TEXTILES WITH GRAPHIC PRINTING AND DECORATION NANO INNOVATION TO THE ECONOMIC COMMUNITIES COMMERCIAL - Theeramongkol, Praparnporn; Sioyraya, Bussara; Hattayananont, Autcha; Pijukkana, Kingkarn; Pigunthong, Darunrat (MATTER: International Journal of Science and Technology, 2017)
This research is design and development of banana fiber textiles with graphic printing and decoration Nano innovation to the Economic Communities Commercial. The results found that Innovative Nano-fiber cloth decorated banana fabric can be antibacterial at 99.95% and staphylococcus bacteria klebsiella pneumonia at 99.93% and water reflection level of 80 percent age, which can be absorbed into the cloth and wet it a bit. The mostly respondents were All have been satisfied at maximum average and highest level of satisfaction that with an average at 4.91 and 98.24 percentage, satisfaction is at the highest level. Execution Technology, the workshop schedule for the two days’ workshop on 17 - 18 September 2559 at the Chedi district office in Suphanburi province, 25 people. Most of the participants were satisfied with the level, in Graphics and decorative nanotechnology innovation, most every question.